2018
DOI: 10.1136/tobaccocontrol-2018-054265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of secondhand smoke and secondhand vapour exposure among youth

Abstract: Almost one-third of Florida youth reported SHV exposure. Factors associated with SHS and SHV exposure are somewhat similar, and exposure to SHS and SHV is associated with tobacco susceptibility in youth. Promoting tobacco-free homes is needed to protect youth from SHS and SHV exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(32 reference statements)
1
11
1
Order By: Relevance
“…In line with a study among youth in the USA,57 our study found that those who perceived SHA as harmful were less likely to report SHA exposure. Generally, people viewed SHA as less harmful than SHS 60.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with a study among youth in the USA,57 our study found that those who perceived SHA as harmful were less likely to report SHA exposure. Generally, people viewed SHA as less harmful than SHS 60.…”
Section: Discussionsupporting
confidence: 91%
“…Exposure to SHA has its impact on social norm and using e-cigarette. Constant SHA exposure among the youth may increase their susceptibility to using e-cigarettes and tobacco products, as well as decreased their harm perception of e-cigarettes 19 57. A higher likelihood of SHA exposure among e-cigarette past users (compared with never users) found in this study may pose a risk of relapse for those who have quit using e-cigarette.…”
Section: Discussionmentioning
confidence: 63%
“…The smoking behavior of adolescents is affected by personal, psychological, and social factors such as gender, smoking behavior of peers or family members and social environment 11,12 . SHS exposure is one of the important risk factors that might increase susceptibility to smoking and nicotine dependence among those who have begun smoking 13 . Prior studies have indicated that SHS could influence tobacco use and smoking behaviors [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, almost 10% of US adolescents reported living with an ENDS user in 2014, 7 and a study among youth in Florida found almost one-third reported secondhand ENDS aerosol exposure. 8 Given that youth with asthma are likely exposed to these aerosols, it is important to understand if and how these exposures affect health. The goal of the present study was to examine the associations between secondhand ENDS aerosol exposure and asthma exacerbations among youth with asthma.…”
mentioning
confidence: 99%